Patient Preferences for Diagnostic Testing in the Emergency Department: A Cross‐sectional Study. (11th June 2018) - Porath, Jonathan D.; Meka, Arjun P.; Morrow, Chelsea; Iyengar, Rahul; Shtull‐Leber, Eytan; Fagerlin, Angela; Meurer, William J
Abstract: Background: Diagnostic testing is common during emergency department (ED) visits. Little is understood about patient preferences for such testing. We hypothesized that a patient's willingness to undergo diagnostic testing is influenced by the potential benefit, risk, and personal cost. Methods: We conducted a cross sectional survey among ED patients for diagnostic testing in two hypothetical scenarios: chest pain (CP) and mild traumatic brain injury (mTBI). Each scenario defined specific risks, benefits, and costs of testing. The odds of a participant desiring diagnostic testing were calculated using a series of nested multivariable logistic regression models. Results: Participants opted for diagnostic testing 68.2% of the time, including 69.7% of CP and 66.7% of all mTBI scenarios. In the CP scenario, 81% of participants desired free testing versus 59% when it was associated with a $100 copay (difference = 22%, 95% confidence interval [CI] = 16% to 28%). Similarly, in the mTBI scenario, 73% of adult participants desired free testing versus 56% when charged a $100 copayment (difference = 17%, 95% CI = 11% to 24%). Benefit and risk had mixed effects across the scenarios. In fully adjusted models, the association between cost and desire for testing persisted in the CP (odds ratio [OR] = 0.33, 95% CI = 0.23 to 0.47) and adult mTBI (OR = 0.47, 95% CI = 0.33 to 0.67) scenarios. Conclusions: In this ED‐based study, patient preferences for diagnostic testing differed significantly across levels of risk, benefit, and cost of diagnostic testing. Cost was the strongest and most consistent factor associated with decreased desire for testing.